Kedisiplinan Belajar Mahasiswa STAI Al-Washliyah Barabai - Indri Yunita (PT. Hasba Edukasi Mandiri, 2026)
This research is motivated by the importance of student learning discipline in supporting the success of the learning process in higher education. Learning discipline is one of the factors that influence student academic quality, such as punctuality in attending lectures, active participation in learning, and responsibility in completing academic assignments. This research uses a qualitative approach with a field research type. The data source for this research is students at STAI Al-Washliyah Barabai. Data collection techniques are carried out through observation, interviews, and documentation. The data analysis techniques use data reduction, data presentation, and drawing conclusions, while the validity of the data is obtained through triangulation of sources and techniques. The results of the study show that the learning discipline of STAI Al-Washliyah Barabai students, namely: 1) Student attendance discipline is quite good because most are present on time and attend lectures regularly. 2) Discipline in doing assignments is also good because students are able to complete and submit assignments according to lecturers' provisions. 3) Discipline in complying with rules is seen from compliance with academic regulations, dress ethics, and polite behavior during learning. 4) Factors supporting discipline include learning motivation, lecturer support, a conducive campus environment, and clear academic regulations. 5) Factors inhibiting discipline include lateness to lectures, organizational activities, part-time jobs, poor time management, and lack of focus while studying. 6) Efforts to improve discipline are carried out through motivation, lecturer supervision, strict implementation of rules, and instilling a sense of responsibility in lectures.